WHO informal consultation on revision of guidelines on evaluation of similar biotherapeutic products, virtual meeting, 30 June – 2 July 2021. (April 2022) - Wadhwa, Meenu; Kang, Hye-Na; Thorpe, Robin; Knezevic, Ivana; ,; Aprea, P.; Bielsky, M.-C.; Ekman, N.; Heim, H.-K.; Joung, J.; Kurki, P.; Lacana, E.; et al.
Abstract: The WHO informal consultation was held to promote the revision of WHO guidelines on evaluation of similar biotherapeutic products (SBPs) adopted by the Expert Committee on Biological Standardization (ECBS) in 2009. It was agreed in the past consultations that the evaluation principles in the guidelines are still valid, but a review was recommended to provide more clarity and case-by-case flexibility. The opportunity was therefore taken to review the experience and identify areas where the current guidance could be more permissive without compromising its basic principles, and where additional explanation could be provided regarding the possibility of reducing the amount of data needed for regulatory approval. The meeting participants applauded the leading role taken by the WHO in providing a much-needed streamlined approach for development and evaluation of SBPs which will provide efficient and cost-effective product development and increase patient access to treatments. It was recognized that the principles as currently described in the draft WHO guidelines are based on sound science and experience gained over the last fifteen years of biosimilar approvals. However, since these guidelines when finalised will constitute the global standard for biosimilar evaluation and assist national regulatory authorities in establishing revised guidance and regulatory practice in this complex area, it was felt that further revision and clarity on certain perspectives in specific areas was necessary to dispel uncertainties arising in the current revised version. This report describes the principles in the draft guidelines, including topics discussed and consensus reached. Highlights: WHO guidelines serve as a basis for the development of national regulatory framework for biosimilars. Revision of guidelines is to provide more flexibility and clarification on data required for regulatory approval. Revised guidelines would contribute to improving consistency on regulatory decision and patient access to treatments.